ARROGANT LEADERSHIP BEHAVIOR AND ITS ROLE IN DEVELOPING ORGANIZATIONAL ZOMBIES IN THE WORKPLACE- EXPLORATORY STUDY IN AL-NAJAF TEACHING HOSPITAL (American Journal of Business Management, Economics and Banking, 2023)
The current study aims to understand the nature of the relationship between conceited leadership behavior and organizational zombies in the workplace at Najaf Teaching Hospital in Najaf Governorate. This is significant because it addresses two critical aspects of the organizational environment and establishes the right foundations and treatments to deal with a real issue that has a direct impact on the working environment in one of the most important institutions in the country. 200 questionnaires were given out to both male and female hospital personnel using the random sample approach by the researcher. The advanced statistical program AMOS.V.24 and the statistical program SPSS v.27 were used to examine the 190 questionnaires that were retrieved and the 182 that were appropriate for statistical analysis, with a response rate of 91% of the retrieved questionnaires. Theoretical findings revealed a knowledge gap about the connection between haughty leadership and workplace zombies in organizations generally and Najaf Teaching Hospital specifically.